Damage Behavior of Cement-Treated Base Material - Nusit K. (2017)
© 2016 The Authors. Published by Elsevier B.V. Cement treated base (CTB) is a cement stabilized material which becomes more important to a modern road pavement under a better performance perspective. However, CTB has the inherent characteristic of fatigue deterioration corresponding to damage evaluations under repeated loading; but relatively rare fatigue and damage studies of CTB have been performed. Therefore, damage developments of CTB specimens tested under different loading conditions were characterized in this study. This because stress/strain state and fatigue life of materials are all related to their damage evolutions. Results from unconfined compressive tests revealed that damage evolutions of CTB specimens depended on the monotonic-compressive loading rates. Moreover, the cyclic flexural beam tests were also performed to determine the fatigue damage evolutions of CTB specimens. The test results showed that damage evolutions of CTB specimens subjected to cyclic bending forces were influenced by the levels of applied strain. However, the damage evolutions were independent from the loading waveforms. In addition, the prediction models for damage evolutions of CTB were also developed in this study. The natural logarithmic model was found to provide the most reliable values of predicted damage variable compared to the other mathematical models used in this study. It was also discovered that regression parameters of the developed model can be estimated by the function of an applied strain level. Furthermore, this study reveals that the fatigue behavior of CTB specimens can be predicted based on the damage variables.